ANALYSIS OF PATTERN AND SEVERITY OF INJURIES IN MEDICO LEGAL CASES PRESENTING TO EMERGENCY DEPARTMENT OF A TERTIARY CARE HOSPITAL: A RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2024)
Medico-legal cases presented to the Emergency Department often involve a diverse range of injuries and understanding the patterns and severity of these injuries is crucial for medical practitioners and the legal authorities. This retrospective study aims to analyse and interpret the nature, distribution, and severity of injuries sustained by individuals in medico-legal cases presenting to the emergency department. A total of 692 medico-legal cases recorded in the medico-legal register of our hospital were included in this study during study period. Data related to patient demographics, injury characteristics, and clinical outcomes were collected and analysed; observed, discussed and compared with other studies. The demographic analysis reveals a predominant occurrence of cases in the age group of 20-40 years (68.49%), with a notable male predominance (79.77%). Seasonal variations indicate a peak in cases during October (16.47%) and reduced incidences during April (1.01%). Road traffic accidents (31.21%) and physical assault (24.85%) emerged as the leading causes, while sexual assault cases were notably absent. Abrasions (43.54%) constitute the most common mechanical injury,
Keywords: Injuries; Medico-legal cases; Tertiary care hospital; Emergency department